A Comprehensive Comparison between WiMAX and Wi-Fi (International Journal of Engineering and Computer Science, 2014)
WiMAX and Wi-Fi are rapidly progressing technologies and now days, it is common to find them not just in laptops and personal digital assistants, but in equipment as mobile phones, parking meters, security cameras and home entertainment equipment. A combination of Wi-Fi and WiMAX deployment, will offer more cost-effective Solution than a sole WiMAX or Wi-Fi implementation and a new technology that solves many of the difficulties in last-mile implementations. WiMAX extends the benefits of Wi-Fi networks to deliver the next-generation mobile Internet. This paper describes two technologies Wi-Fi (Wireless Fidelity) & WiMAX (Worldwide Interoperability for Microwave Access) used in wireless communication along with their comparison.